Antiplatelet Therapy in the Secondary Prevention of Non-cardioembolic Ischemic Stroke and Transient Ischemic Attack: A Mini-Review - Vališ, Martin; Klímová, Blanka; Novotný, Michal; Herzig, Roman (Frontiers in Neurology, 2021)
The aim of this mini-review is to discuss the main antiplatelet agents that have been successfully used in the secondary prevention of non-cardioembolic ischemic stroke and transient ischemic attacks (TIA). The methodology is based on a literature review of available peer-reviewed English studies listed in PubMed. The findings reveal that aspirin remains a reliable antiplatelet agent in the secondary prevention of acute non-cardioembolic ischemic stroke and TIA. Nevertheless, currently, there are also other agents, i.e., ticagrelor, clopidogrel, and cilostazol, that can be applied. In addition, the results indicate that time is significant not only in severe stroke but also in non-severe stroke and TIA, which suggests that antiplatelet therapy should be applied within 24 h after the first symptoms because early treatment can lead to an improvement in neurological outcomes and reduce the chance of an early subsequent stroke.